2017
DOI: 10.1016/j.ypmed.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The association between beliefs about vitamin D and skin cancer risk-related behaviors

Abstract: Major health organizations recommend obtaining most of one’s vitamin D through dietary sources rather than from sun exposure, given the link between sun exposure and increased skin cancer risk. The purpose of this study is to examine the association between beliefs about vitamin D and skin cancer risk-related behaviors, a topic on which research is limited. We analyzed cross-sectional online survey data collected in the summer of 2015 from 4127 U.S. adults aged 18 years and older. Overall, 19.7% of adults beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
2
12
0
1
Order By: Relevance
“…Analysis of this data was exempt from institutional review board approval because CDC did not engaged in human research and personal identifiers were not included in the data file. Additional information about the study sample can be found in a previous study using the 2015 Summer ConsumerStyles data (Holman et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Analysis of this data was exempt from institutional review board approval because CDC did not engaged in human research and personal identifiers were not included in the data file. Additional information about the study sample can be found in a previous study using the 2015 Summer ConsumerStyles data (Holman et al, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Recently only 43.1% of US adults agreed that vitamin D sufficiency is possible by diet and supplementation alone, a belief that was associated with increased sun protection. 9 In contrast, the belief that tanning effectively increases vitamin D was associated with increased indoor and outdoor tanning. Further, seasonal depressive symptoms have been documented in 80% of frequent indoor tanners.…”
Section: Introductionmentioning
confidence: 99%
“…A large study ( n = 4127) conducted in the USA explored the interaction between vitamin D beliefs and skin cancer risk-related activities. This was a cross-sectional retrospective study using online survey data derived from a larger study [20]. Approximately 20% of participants were 55–64 y/o, and 20% were 65 y/o+.…”
Section: Resultsmentioning
confidence: 99%
“…Although in most studies a significant proportion of older adults could identify some dietary vitamin D sources, and in selected studies older people were more knowledgeable about food sources of vitamin D compared with younger participants (for example [15,16,17,18]), a significant number of older people misidentified certain foods as good sources of vitamin D, or assumed that a “balanced diet” would ensure adequate intake of vitamin D [26]. The finding in one large study conducted in the USA that the majority of older adults surveyed felt that their diet and vitamins provide adequate vitamin D, whilst multiple national dietary surveys have consistently documented both low intakes and low blood levels in a significant minority of older adults, also suggests misinformation about vitamin D containing foods [20]. Low vitamin D status is a persistent problem amongst older adults, and in order to enable older adults to make informed choices to improve dietary intake, healthcare professionals and public health bodies need to develop dietary guidelines that clearly identify vitamin D rich foods, and effective communication strategies for disseminating these guidelines specifically targeted towards older people.…”
Section: Discussionmentioning
confidence: 99%